Evaluasi Kinerja Saluran Irigasi Daerah Irigasi Rawa Kumpeh Desa Maju Jaya Kabupaten Muaro Jambi - Alyadi, Muhammad; Aswandi, Aswandi; Syarif, Syarif (Universitas Batanghari Jambi, 2024)
The Rawa Kumpeh Irrigation Area is one of the swamp irrigation areas that is still actively operating in Muaro Jambi Regency. In the management of swamp irrigation areas in this area, namely the performance of the swamp irrigation area itself, which includes the availability of water obtained from the tides of the Kumpeh River as well as the need for irrigation water for food crops, namely rice and secondary crops developed in the swamp area. Apart from that, the main thing about Tidal Swamp Irrigation is water management with a Water Gate Operation System. The aim of this research is to determine the performance conditions of Swamp Irrigation Areas, especially DIR. Kumpeh Swamp which can provide input in managing the swamp irrigation network. The data collection methodology was carried out by means of interviews, literature studies and field surveys. The results of this research can be concluded that the network performance value at the research location is 70.00% - 90.00% for performance. Condition is in the good category (functions well, no significant damage was found). Includes Primary, Secondary SK 1, Channel Types. SK.2, SK.3, SK.4, and SK.5 Block E, the network performance value at the research location is 55.00 % - 69.00 % for performance Condition in the Medium Category (functional, found there is damage but can resolved and put into operation) Includes Secondary Block E SK.4, while for the buildings at the research location, there are 3 (three) sluice gates with sliding doors in fairly good condition with the building performance assessment results averaging 82.81 % where the results of the performance value are included in good performance (70 - 90%). The performance value of the canals and buildings at the research location can also be concluded as the magnitude of the benefit value of the canals and buildings, in relation to the area of agricultural services that utilize these canals and buildings to irrigate agricultural land.